EMSIAC Wars: Re-inserting the Human in Bernard Wolfe's Limbo. Issue 3 (1st December 2020) - Ryder, Mike
Abstract : Bernard Wolfe's dystopian satire Limbo (1952) remains a critically under-discussed work, and despite its many controversies, offers important insight into the ethical dilemmas surrounding modern-day drone warfare and human-machine relations. While the EMSIAC war computers in Limbo may be blamed for World War III, they are only ever a scapegoat to shift blame away from the humans who follow orders blindly, and themselves behave much like machines. To this end, this paper will explore the ethical implications of Wolfe's novel and what it means for the way we wage wars with robotic drones controlled by humans from afar.